A Model for the Growth of Self-Concept - Guest, Gerald R.; Thomson, Eric W. (Canadian Journal of Counselling and Psychotherapy, 1972)
Teachers must play a more consciously active role in fostering healthy self-esteem in children. To make such action more likely to occur successfully, a model is presented to conceptualize the dynamics of growth in positive self-concept, incorporating the notions of awareness, mastery, and reinforcement in a communication framework of positive feedback.